COVID-19 challenges in clinical trials - Panchatcharam, Murugan; Mukku, Sravanthi Lakshmi (International Journal of Basic & Clinical Pharmacology, 2021)
Clinical research involves working with human subjects to answer questions relevant to their well-being in an ethical manner. The current scenario from the past one year has drastically changed the face of the clinical trials. The present COVID prevalence and simultaneously conducting the research with all the regulations and the precautions has been the difficult task for the contract research organisations (CRO).